Captain Johan Heitman, DEN GYLDNE LØVE and the Danish Silver Robbery - O´Rourke, Andrew (M/S Museet for Søfarts årbog, 2017)
In 1730 the Danish ship DEN GYLDNE LØVE (THE GOLDEN LION) bound for Tranquebar was wrecked on the west coast oflreland. The crew were rescued and taken ashore and the shiifs outward-bound camo ofSi)anish silver dol- 1 O J 1 lårs, to a value of about 76,000 rix- dollars, was salvaged and lodged with the local residents in the neighbourhood. However, the money was stolen, and although it was widely known who the thieves were the matter became a political issue. For many years Asiatisk Kompagni tried to regain the money, and it was not until March 1740 that Johan Heitman could return to Copenhagen. The money, hoiuever, was never recovered. Based on English and Danish sources Mr. Andrew ORourke, the Irish ambassador to Denmark, reviews this Strange case in an article which, contrary to our normal practice, is printed in English with a Danish summary.